(untitled) (Sebha University Conference Proceedings, 2024)
Understanding rock properties and rock behavior under varying conditions is essential for predicting and managing rock behavior across different engineering applications. This study focuses on how rock properties respond to temperature variations, specifically through Microwave Irradiation (MI) and Shock Cooling (SC), and the implications of these changes for civil engineering, oil and gas drilling, and mining. In civil engineering, such knowledge is vital for designing stable and durable foundations. In drilling and excavation, altering rock properties to weaken rocks can enhance drilling efficiency, increase the Drilling Rate of Penetration (ROP), and reduce operational costs. The objective of this review is to consolidate research findings on the impact of MI and SC on rock properties, such as mechanical strength and mineral composition. By assessing these studies, the review aims to identify the potential benefits of using MI and SC to improve drilling performance, extend the lifespan of drill bits, and minimize drilling expenses. The review also explores the mechanisms through which these temperature-induced treatments create micro-fractures that facilitate easier drilling. In conclusion, the compiled research demonstrates that both MI and SC can significantly alter rock properties, offering practical applications in drilling and excavation. These techniques can effectively reduce rock strength, leading to improved ROP and cost savings in drilling operations. The insights provided by this review could guide future developments in engineering practices, particularly in enhancing the efficiency and sustainability of drilling activities.